PEDAGOGICAL INTERNSHIP IN THE CYCLIC PROCESS OF STUDENT TEACHERS’ TRAINING - Fedorenko, Svitlana; Tikan, Yana; Kolomiiets, Svitlana (Theoretical and Methodical Problems of Children and Youth Education, 2021)
The article highlights the courses which provide theoretical grounds for the pedagogical internship in the cyclic process of student teachers’ training at the faculty of linguistics of the National Technical University of Ukraine “Igor Sikorsky Kyiv Polytechnic Institute” (hereinafter officially abbreviated name – Igor Sikorsky KPI). The study design was narrative and analytical, exploiting the following methods: system analysis of methodological sources, generalization of positive experience of the cyclic process of student teachers’ training through the pedagogical internship, monographic method – to cover the findings obtained. It is stated that the effectiveness of training future teachers at the technical university to a large extent depends upon developing this process into a meaningful instructional enhancement with pedagogical internship as the concluding stage. Student teachers’ training cyclic process is designed to enhance: the quality of results-driven professional growth; professional collaboration between staff and students as well as among students themselves; arrangement of curriculum, educational and assessing processes to the standards; quality, coherence and monitoring of students’ learning process across classroom and extra-curricular activities. The three-fold aim of the pedagogical internship is outlined: firstly, to practice and improve student teachers’ skills through the classroom practice; secondly, to develop the unique pedagogic style of every student teacher; thirdly, to promote positive changes in students learning that provide the theoretical basis for pedagogical internship as well as monitoring the process of pedagogical internship, assessing the progress (self-assessment including), eliminating certain drawbacks, and providing the feedback. The pedagogical internship is considered a coherent element of the curriculum contributing to the process of students’ socializing, understanding educational phenomena as well as forming students’ competence-based skills of pedagogical activities.